Molecular Diagnosis of Bacterial Infective Endocarditis in Tabriz, Azerbaijan - Ghotaslou, Reza (Tabriz University of Medical Sciences, 2013)
Introduction: The aim of this study was to analyze a PCR based approach for detection of infective endocarditis in Azerbaijan. Methods: Ten aortic valves, 8 mitral valves and 2 tricuspid valves, were analyzed for the presence of bacterial infective endocarditis using Gram staining, culture and PCR methods. Results: Of the 20 valves, 5 and 4 cases were positive by Gram staining and culture assay, respectively. Bacterial DNA was positive in 12 of the 20 valves (60%) by broad-spectrum PCR. Direct sequencing for species identification was possible in 10 cases. Conclusion: PCR and direct molecular identification of the etiological agents responsible for infective endocarditis may enable specific treatment to begin at an earlier phase of the disease.